A case of recto-vaginal obstetrical fistula treated by the Martius lamp, seen at Befelatanana Madagascar - Lanto, Rainibarijaona; Martial, Rakotonirina; Besaina, Rakotozanany; Tanjona, Ratsiatosika; Romuald, Randriamahavonjy; Hery, Andrianampanalinarivo Rakotovao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
The rectovaginal fistulas are a pathological epithelialized communication between the vagina and the rectum, its frequency is 10 to 30%, and it is a disabling pathology because of the social repercussion. Many flap techniques have been described but the aim is to present a simple procedure according to a particular technique called Martius. This is a case of woman presenting a low rectovaginal fistula on obstetrical trauma. The surgical technique consists of a repair according to the technique of Martius. The operative follow-up was simple and the patient was able to resume sexual activity and normal anal sphincter function. It is a simple technique, easy to achieve for the technical platform in Madagascar whose evaluation of the results for a larger population should be considered. This technique therefore deserves to be known and widely used.